ETIKA DAN INTEGRITAS POLISI - Oktiane Bulan Indah, Wulan Febianty, Zalfaa Hafiz Anabresta, Sulistiasih (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Good public service and law enforcement are essential toining national order and security. This study investigates how police ethics and integrity relate to analyzing the concepts of police ethic and integrities. The objective of this study is to understand the important role played by moral values and Integrity in police operations. This study aims to explain how ethics, integrity, and honesty can be incorporated into police practice to improve the quality of public service and strengthen the relationship between police and society. This research uses qualitative methodology to do it.